Comparison of electrostatic and localized plasmon induced light enhancement in hybrid InGaN/GaN quantum wells - Lin, Jie (2017)
The light enhancement phenomena in InGaN/GaN multi-quantum wells (MQWs) infiltrated with metal nanoparticles (NPs) are studied using resonant and off-resonant localized plasmon interactions. The emission and recombination characteristics of carriers in InGaN/GaN MQW structures with inverted hexagonal pits (IHPs) are modified distinctly depending on the nature of their interaction with the metal NPs and with the pumping and emitted photons. It is observed that the emission intensity of light is significantly enhanced when the emission energy is off-resonant to the localized plasmon frequency of the metal nanoparticles. This results in enhanced emission from MQW due to Au nanoparticles and from IHPs due to Ag nanoparticles. At resonant-plasmon frequency of the Ag NPs, the emission from MQWs is quenched due to the re-absorption of the emitted photons, or due to the drift carriers from c-plane MQWs towards the NPs because of the Coulomb forces induced by the image charge effect. (C) 2014 AIP Publishing LLC.